1996
DOI: 10.1055/s-2006-957862
|View full text |Cite
|
Sign up to set email alerts
|

In VitroAnticancer Activity of Fruit Extracts fromVacciniumSpecies

Abstract: Fruit extracts of four Vaccinium species (lowbush blueberry, bilberry, cranberry, and lingonberry) were screened for anticarcinogenic compounds by a combination of fractionation and in vitro testing of their ability to induce the Phase II xenobiotic detoxification enzyme quinone reductase (QR) and to inhibit the induction of ornithine decarboxylase (ODC), the rate-limiting enzyme in polyamine synthesis, by the tumor promoter phorbol 12-myristate 13-acetate (TPA). The crude extracts, anthocyanin and proanthocya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
160
1
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 258 publications
(165 citation statements)
references
References 0 publications
1
160
1
3
Order By: Relevance
“…The most striking antioxidant activity is cyaniding 3-galactose. DPPH assays showed that it was more effevtive than flavonol glycoside and the standards in scavenging free radicals, with an EC50 of 7.7 M compared to 17.3 M for myricetin 3-arabinoside and 30 M for trolox standard [4,130,131] Increased plasma antioxidant status, protected RBC against hemolysis [126,132] Showed protective effects on PC12 cells damage and chronic diseases associated with oxidative stress [133] Showed neuro and mitochondrio-protective effect [134] Antioxidant Activities Showed antioxidative activity under the used assay conditions towards prevention of oxidative DNA damage [135] Inhibited proliferation of MCF-7, MDA-MB-231 and MDA-MB-435 breast cancer cells [4,8,126,127] Inhibited the induction of ornithine decarboxylase, an enzyme involved in tumor proliferation, and induce quinine reductase, an enzyme that can inactivate certain carcinogens [136] Exhibited the human colon tumor cell lines Caco-2, HT-116, and HT-29 [10,137,138] Exhibited the anticancer effects on DLD-1 and COLO205 cells [139] Inhibited matrix metalloproteinase activity in DU145 human prostate cancer cells [140] Exhibition of anticancer capability in human lung and leukemia cells [105] Modulated the expression of cyclooxygenase-2 (COX-2) and I B in human colon cancer cells [141] Cytotoxicities Inhibitory effect on activator protein-1, nuclear factor-B, and mitogen-activated protein kinases activation [105,142] Prevented the urinary tract infections [143] Showed potential inhibitory effect against bacteria involved in dental caries and periodontal diseases [147,148] Exhibited potent biological activity by inhibiting adherence of uropathogenic isolates of P-fimbriated Escherichia coli bacteria to cellular surfaces containing -Gal(1 4)--Gal receptor sequences similar to those on epithelial cells in the urinary tract [149,150] Antimicrobial Activities…”
Section: Biosynthesis Pathways Of Anthocyanins and Flavonoids (Figmentioning
confidence: 99%
“…The most striking antioxidant activity is cyaniding 3-galactose. DPPH assays showed that it was more effevtive than flavonol glycoside and the standards in scavenging free radicals, with an EC50 of 7.7 M compared to 17.3 M for myricetin 3-arabinoside and 30 M for trolox standard [4,130,131] Increased plasma antioxidant status, protected RBC against hemolysis [126,132] Showed protective effects on PC12 cells damage and chronic diseases associated with oxidative stress [133] Showed neuro and mitochondrio-protective effect [134] Antioxidant Activities Showed antioxidative activity under the used assay conditions towards prevention of oxidative DNA damage [135] Inhibited proliferation of MCF-7, MDA-MB-231 and MDA-MB-435 breast cancer cells [4,8,126,127] Inhibited the induction of ornithine decarboxylase, an enzyme involved in tumor proliferation, and induce quinine reductase, an enzyme that can inactivate certain carcinogens [136] Exhibited the human colon tumor cell lines Caco-2, HT-116, and HT-29 [10,137,138] Exhibited the anticancer effects on DLD-1 and COLO205 cells [139] Inhibited matrix metalloproteinase activity in DU145 human prostate cancer cells [140] Exhibition of anticancer capability in human lung and leukemia cells [105] Modulated the expression of cyclooxygenase-2 (COX-2) and I B in human colon cancer cells [141] Cytotoxicities Inhibitory effect on activator protein-1, nuclear factor-B, and mitogen-activated protein kinases activation [105,142] Prevented the urinary tract infections [143] Showed potential inhibitory effect against bacteria involved in dental caries and periodontal diseases [147,148] Exhibited potent biological activity by inhibiting adherence of uropathogenic isolates of P-fimbriated Escherichia coli bacteria to cellular surfaces containing -Gal(1 4)--Gal receptor sequences similar to those on epithelial cells in the urinary tract [149,150] Antimicrobial Activities…”
Section: Biosynthesis Pathways Of Anthocyanins and Flavonoids (Figmentioning
confidence: 99%
“…The content and composition of anthocyanins in bilberries, as well as in blueberries, has been determined earlier by Suomalainen and Keränen (1961), Martinelli et al (1986), and Wang et al (2000). Several studies have also been done on the bioactive properties of bilberries and blueberries (Bomser et al, 1996;Kalt and Dufour, 1997;Youdim et al, 2000), especially concerning the antioxidant activity of their anthocyanin fractions (Prior et al, 1998;Smith et al, 2000;Ehlenfeldt and Prior, 2001). However, to our knowledge, there are no published studies on flavonoid biosynthesis in blueberries with particular regard to the expression of genes in the phenyl propanoid pathway.…”
mentioning
confidence: 97%
“…Anthocyanin, a reddish plant pigment, is a kind of flavonoid distributed widely in colored fruits and vegetables, including eggplants, 4) black currants, 5) grapes 6) and blueberries. 7,8) As with other flavonoids, the phytoceutical significance of anthocyanins has been discussed in relation to a wide range of physiological functions such as vision improvement, 9,10) anticancer activity, 11,12) and antioxidant activity. [13][14][15][16][17] Capillary electrophoresis (CE) has been successfully used in addition to HPLC to analyze flavonoids.…”
mentioning
confidence: 99%